2017
DOI: 10.32607/20758251-2017-9-2-47-58
|View full text |Cite
|
Sign up to set email alerts
|

C2H2 Zinc Finger Proteins: The Largest but Poorly Explored Family of Higher Eukaryotic Transcription Factors

Abstract: The emergence of whole-genome assays has initiated numerous genome-wide studies of transcription factor localizations at genomic regulatory elements (enhancers, promoters, silencers, and insulators), as well as facilitated the uncovering of some of the key principles of chromosomal organization. However, the proteins involved in the formation and maintenance of the chromosomal architecture and the organization of regulatory domains remain insufficiently studied. This review attempts to collate the available da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 135 publications
(169 reference statements)
2
135
0
4
Order By: Relevance
“…The KRAB domains are widely present in human zinc finger proteins, and considered as potent transcriptional repression modules through interacting with KAP1 and subsequently recruiting histone-modifying proteins (11,33,34). ZNF677, a member of KRAB zinc finger protein family, is only reported to be downregulated by promoter methylation in NSCLC (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KRAB domains are widely present in human zinc finger proteins, and considered as potent transcriptional repression modules through interacting with KAP1 and subsequently recruiting histone-modifying proteins (11,33,34). ZNF677, a member of KRAB zinc finger protein family, is only reported to be downregulated by promoter methylation in NSCLC (12).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger proteins are the largest transcription factor family in human genome, which have a wide variety of functions in human diseases including cancers through transcriptionally activating or repressing their targets (10). The majority of zinc finger proteins contain Kr€ uppel associated box (KRAB) domains, which has been demonstrated to repress the transcription of their downstream targets (11). As a member of the Kr€ uppel C2H2-type zinc finger protein family, the zinc finger protein 677 (ZNF677) is the least studied, and is only found to be methylated in non-small cell lung cancer (NSCLC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…The ZNF622 protein contains C 2 H 2 zinc finger motifs (Fig. 1B), which are putative DNA-binding modules (57). This prompted us to analyze whether the reintroduced ZNF622(wt)-HA could interact with viral DNA.…”
mentioning
confidence: 99%
“…Finally, we explored the functional significance of the carbonylation of zinc fingers and showed that the ERR family of nuclear receptors are carbonylated in vivo, and this leads to a severe impairment in DNA-binding capacity. Zinc fingers are most commonly observed in DNA-binding proteins and are critical for sequence-specific DNA binding of a wide variety of proteins involved in transcription, replication, and repair (49,50). It is appreciated that these proteins are sensitive to oxidative stress, although the mechanisms by which this occurs remain elusive (34,51).…”
Section: Nuclear Carbonylation Of Zinc Finger Proteinsmentioning
confidence: 99%